2012
DOI: 10.1002/arch.21069
|View full text |Cite
|
Sign up to set email alerts
|

IDENTIFICATION AND CHARACTERIZATION OF TWO SENSORY NEURON MEMBRANE PROTEINS FROM Cnaphalocrocis medinalis (LEPIDOPTERA: PYRALIDAE)

Abstract: Sensory neuron membrane proteins (SNMPs), which are located on the dendritic membrane of olfactory neurons, were considered as important components involved in pheromone reception in insects. In Drosophila melanogaster, mutants without SNMP are unable to evoke neuronal activities in the presence of pheromone cis-vaccenyl acetate (cVA). So deeply understanding the SNMPs functions may help to develop pheromone-mediated insect pest management tactics. The present study reports the identification and characterizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
27
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 26 publications
(57 reference statements)
6
27
2
1
Order By: Relevance
“…Amino acid sequence comparison shows that SlituSNMP1 and SlituSNMP2 have all the characteristics of SNMPs, especially two transmembrane domains, as well as six conserved cysteines suggested to form disulfide bridge in the large central extracellular loop (Rasmussen et al ., ). Phylogenetic analysis indicates that the insect SNMPs, which are structurally different from odorant receptors (Krieger et al ., ; Krieger et al ., ; Nakagawa et al ., ; Wang et al ., ), are divided into two clear subgroups, SNMP1 and SNMP2, similar to previous reports (Nichols & Vogt, ; Vogt et al ., ; Liu et al ., ; Liu et al ., ). Furthermore, in each of the two subgroups, the SNMPs from different Lepidoptera species cluster together, forming a clade distinct from SNMP homologues of Coleoptera, Diptera and Hymenoptera.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amino acid sequence comparison shows that SlituSNMP1 and SlituSNMP2 have all the characteristics of SNMPs, especially two transmembrane domains, as well as six conserved cysteines suggested to form disulfide bridge in the large central extracellular loop (Rasmussen et al ., ). Phylogenetic analysis indicates that the insect SNMPs, which are structurally different from odorant receptors (Krieger et al ., ; Krieger et al ., ; Nakagawa et al ., ; Wang et al ., ), are divided into two clear subgroups, SNMP1 and SNMP2, similar to previous reports (Nichols & Vogt, ; Vogt et al ., ; Liu et al ., ; Liu et al ., ). Furthermore, in each of the two subgroups, the SNMPs from different Lepidoptera species cluster together, forming a clade distinct from SNMP homologues of Coleoptera, Diptera and Hymenoptera.…”
Section: Discussionmentioning
confidence: 99%
“…A similar expression pattern was also found for ApolSNMP1 and ApolSNMP2 on the antennae of male Antheraea polyphemus (Forstner et al ., ). Recently the SNMPs in Cnaphalocrocis medinalis , Agrotis ipsilon and S. exigua have been identified and discussed (Liu et al ., ; Gu et al ., ; Liu et al ., ). The exact function of SNMPs in moths is still unknown, but the essential role in pheromone reception in D. melanogaster and the broad expression in pheromone sensing sensilla indicate they may be involved in pheromone detection in Lepidoptera.…”
Section: Introductionmentioning
confidence: 98%
“…Since then, much progress has been achieved in the identification of SNMP1 and SNMP2 in different insect orders. 103,119,[126][127][128][129][130][131][132][133] ApolSNMP1 mRNA expression increased significantly 1-2 days before adult emergence, coinciding with the functional maturation of the olfactory system. The abundant expression of SNMP1 in pheromonespecific olfactory neurons suggests it may be involved in pheromone detection.…”
Section: Sensory Neuron Membrane Proteinsmentioning
confidence: 93%
“…136,137 This was the first demonstration of SNMP functions in vivo. Additionally, it has been reported that SNMPs display wide expression patterns in different tissues, [129][130][131][132][133] suggesting that they may be involved in some functions beyond olfactory detection.…”
Section: Sensory Neuron Membrane Proteinsmentioning
confidence: 99%
“…Two SNMP subfamilies, SNMP1 and SNMP2, have been identified in insects (Nichols & Vogt, 2008); in addition, a novel lepidopteran SNMP, SNMP3, has recently been characterized (Zhang et al, 2018). Since then, diverse SNMP1 and SNMP2 homologues have been identified across insect species (Li & Qin, 2011;Liu et al, 2012;Xiao et al, 2017). Since then, diverse SNMP1 and SNMP2 homologues have been identified across insect species (Li & Qin, 2011;Liu et al, 2012;Xiao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%